UNDERSTANDING THE INFLUENCE OF FOOD VALUE ON FAST-FOOD CUSTOMER BEHAVIOR: A STUDY ON THE MEDIATING ROLE OF BLOGGER REVIEWS AND MODERATING EFFECT OF CONTENT CREDIBILITY - Foda M. AISHA; Amany E. SALEM; Muhanna Y. ALMAKHAYITAH; Khaled GHAZY; Hisham M. AL-SMADI; Maria GOZNER; Mohamed A.S ELSAYED (Geo Journal of Tourism and Geosites, 2024)
This study proposes investigating the effect of food value on food bloggers' reviews (i.e., the direct effect) and the customers' purchase intentions (i.e., the direct and indirect effects) of fast-food restaurants. In addition, this study examines the moderating role of content credibility on food blogger reviews and customers' purchase intention relationships. The quantitative method is used in this study to gather data from fast-food restaurant customers in Cairo, Egypt. Where 450 questionnaires were given out to fast-food restaurant customers, 354 valid questionnaires were gathered for analysis. The data were analyzed using SPSS and Amos software. Food value positively influences food bloggers' reviews and fast-food restaurant customers' purchasing intentions. Additionally, this research found that food blogger reviews mediate a positive relationship between food value and fast-food restaurant customers' intentions to purchase. Importantly, this study discovered that content credibility has a positive moderating impact on the relationship between food blogger reviews and the purchase intention of fast-food restaurant customers. The study contributes to the literature on tourism and hospitality, where we employed food value as a decisive and influencing factor in improving food bloggers' reviews and thus influencing fast-food restaurant customers' intention to purchase. Thus, fast-food restaurant managers should create all the suggested food values because of their impact on food bloggers' reviews and customers' intentions to purchase.